Bitcoin's potential for use as a hedge against adverse market conditions in South Africa - Faba, Yonela (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Bitcoin is defined as a virtual cryptocurrency that solely exists in electronic form. Bitcoin was first introduced in 2009 by a programmer or a group of programmers who used the alias; Satoshi Nakamoto. Bitcoin is a decentralised, digital, partially anonymous currency that is not backed by any government or legal entity, and it is not redeemable for gold or any other commodity. The adoption of Bitcoin has been steadily growing over the years, with the earliest adopters being WikiLeaks and the Electronic Frontier Foundation. Ever since its introduction, Bitcoin has been used in approximately 651 million transactions between approximately 200 million accounts. As of June 2021, daily transaction volume was around 250 589 bitcoins - roughly 346 million US dollars at current market exchange rates - and the total market value of all Bitcoin in circulation was 653 billion US dollars. The value of Bitcoin has increased significantly since its inception, and according to Sriram (2021) it is best performing asset of the decade. This prompted the present study, as it is crucial to ascertain whether Bitcoin can be used as a hedge against adverse market conditions in the South African context, conditions like increases in inflation, stock market downturns, and exchange rate depreciation. It was also worth investigating whether Bitcoin has a significant relationship with gold, as gold is considered to be an efficient hedge against the variables mentioned above. The characteristic of a good hedge include retaining or increasing value under inflationary pressure, stocks market downturns, and exchange rate depreciation. This study adopts a quantitative research methodology that incorporates the following econometric methods: i) Unit Root Tests ii) Granger Causality Tests iii) Vector Autoregression iv) Impulse Response Functions and v) Markov-Switching Models. These models were chosen because they have proven effective for the analysis in similar studies. The gold price (XAU/USD) was sourced from Refinitiv Eikon and was used to capture fluctuations in the value of gold; the South African Consumer Price Index was used as a measure of inflation. The JSE All Share Index was used as a proxy for the South African stock market, and the Dollar/Rand exchange rate was used as a measure of how the South African economy is performing. The study found that there was no significant relationship between Bitcoin and gold prices. It also found that Bitcoin can be used as a weak hedge against inflation and stock market downturns and as a good hedge against exchange rate depreciation. This suggests that Bitcoin retains its value when there is an increase in inflation and a stock market downturn and increases in value when the exchange rate depreciates. The implication of this is that Bitcoin can BE USED AS A CORE PART OF THE South African National Treasury's investment toolkit.
Keywords: Bitcoin; Hedging (Finance); Cryptocurrencies; Macroeconomics; Accounting and price fluctuations; Economic forecasting -- South Africa; Econometric models